Realizacja edukacji zdrowotnej w szkołach podstawowych i ponadpodstawowych z perspektywy doświadczeń i oceny studentów - Leksy, Karina; Skowrońska-Pućka, Agnieszka; Nawój-Połoczańska, Joanna (Studia Edukacyjne, 2024)
Health education is an essential component of health promotion, constituting a process through which individuals and communities learn to prioritize and maintain their own and others’ health. Furthermore, it constitutes a pedagogical and didactic process conducted at all levels of education. It is unfortunate that, given that health education is integrated into other teaching subjects in Poland, there may be considerable doubt as to its reliable implementation and effectiveness. This article presents the findings of a study conducted among students regarding their experiences and perceptions of the implementation of health education at the primary and secondary school levels. The findings of the research demonstrate that health education was implemented in only 30% of cases at both levels of education. Furthermore, the content of these instances was limited to traditional topics related to a healthy lifestyle, without consideration of the numerous other factors that contribute to human health. Consequently, there is a pressing need to introduce health education as a separate subject, taking into account the socio-cultural and environmental contexts.